Selected Chapters of English Philology - (:unkn) unknown (Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education, 2021)
According to the curriculum, students at the College have to study both theoretical and practical disciplines that are the integral parts of the training program for English major bachelor students. These disciplines cover a wide range of philological orientation starting with the very origins of the history of the English language. The theoretical courses are offered to students over the four years of the studies for a bachelor degree at the College. Then, in the Masters’ course, students are offered a possibility to revise the theoretical knowledge that the studied disciplines provided for them and widen and deepen this knowledge within the frames of the course titled “Selected Chapters of the English philology”. The course aims at clarifying all those issues that were not examined or discussed in detail during the theoretical disciplines (e.g. issues in lexicography). By the end of the program, participants will have reviewed, synthesized and expanded the knowledge that was covered during the theoretical courses of their studies (namely, The History of English, Phonetics and Phonology, and Lexicology). In addition, students will have had the opportunity to examine issues that were not covered in the theoretical courses and will have had the chance to explore the most crucial questions. The aims of the course are: review and summarize the most outstanding and memorable CHAPTERS of the development of English; examine in details theoretical issues that were not thoroughly analysed in the course of the studied theoretical disciplines at the bachelor level; investigate questions that were left out from the core syllabi of the theoretical disciplines because of the defined time limit at the bachelor level.
Method Guide for MA students
Вибрані розділи англійської філології
Keywords: English Philology; Method Guide; MA students